Insights into the solvation of vanadium ions in the vanadium redox flow battery electrolyte using molecular dynamics and metadynamics - Gupta, Sukriti (2020)
The interaction of vanadium ions (V2+, V3+, VO2+ and VO2+) with counter ions in the condensed-phase vanadium redox flow battery (VRFB) system is investigated using force-field based molecular dynamics (MD), coupled with well-tempered metadynamics (WT-MetaD). In the conventional VRFB electrolyte, (i) bisulphate ions are found relatively less stable in the first solvation shell of vanadium ions than in the bulk, and (ii) the free energy of sulphate ions in the first solvation shell of vanadium ions is marginally lower than that in the bulk. Thus, significant proportion of vanadium ions in the conventional VRFB will have an undisturbed water coordination sphere. The presence of additives like hydrochloric acid and phosphate salts introduces chloride and dihydrogen phosphate ions into the electrolyte. These counter ions are found to be significantly more stable in the first solvation shell of vanadium ions, thereby modifying their local solvation structure by replacing water molecules. The activation free energy barriers for the diffusion of all counter ions into the first solvation shell of vanadium ions can be overcome at room temperature. We believe that the MD + WT-MetaD tool, as presented here, can be used to screen and select potential additives for enhancing the solubility of vanadium ions in VRFB.